Fluidos em Espaços Não-Comutativos - Holender, Luiz (2011)
In this work, we present the results of our research on the generalization of the relativistic fluids in the K¨ahler parametrization to noncommutative spaces by applying methods of field theory. Our proposal can be applied to a large class of fluid models parametrized by two arbitrary smooth functions that generalize the K¨ahler potential on the surface of complex potencials of fluids and the parameter function of the state equation, respectively. We determine the constraints that the degress of freedom of the fluid should satisfy in order to have the fundamental symmetries of the noncommutative geometry and calculate the physical quantities of the noncommutative fluid.